PENGARUH DISIPLIN DAN KOMITMEN TERHADAP KINERJA KARYAWAN PADA PT. ASRINDO CITRASENI SATRIA DI PEKANBARU - Sri Anggraini Sri Anggraini; Gimin Gimin '; Fenny Trisnawati Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the effect of discipline and commitment to employee performance at PT. Asrindo Citraseni Satria in Pekanbaru. This research was conducted at PT. Asrindo Citraseni Satria in Singapore from May 2015 through October 2015. The research method used is descriptive quantitative method. Population of more than 35 employees, including the manager and the sampling technique using saturated sample. Data collection instruments used were a questionnaire with Likert scale for the independent variables: the discipline (X1) and commitment (X2). Data analysis technique used is multiple linear regression. The result showed that the discipline and commitment to simultaneously affect the performance of employees at PT. Asrindo Citraseni Satria in Pekanbaru. This is based on the results of analyzes, calculations show F count> F table (46.941> 3.29). While partially, disciplined significant effect on the performance of employees at PT. Asrindo Citraseni Satria in Pekanbaru and commitments had no significant effect on the performance of employees at PT. Asrindo Citraseni Satria in Pekanbaru. This is evidenced by uni t, discipline variables obtained t 4.401> t table 1.69389 and variables obtained commitments 1,234 t <t table 1.69389. From the calculation of the coefficient of determination of discipline and commitment both have an influence on the performance of employees at PT. Asrindo Citraseni Satria by 74,6% and the remaining 25,4% are influenced by other factors not examined.Keywords: influence, discipline, commitment, employee performance